Assessing SIKS-NG for Poverty Data Management in Social Welfare - Aprilia, Melly Nia Dwi; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2024)
The Specific background shows that although many E-Government applications have been implemented, the effectiveness of the next generation social welfare information system (SIKS-NG) in processing poverty data at the village level is still poorly understood. Knowledge gap raises questions about how SIKS-NG can be optimized to meet social welfare objectives. The aim of this study is to evaluate the performance of SIKS-NG as a poverty data processing application and identify the challenges faced in its implementation. Results of the study show that accuracy in determining program targets, lack of effective socialization, and inadequate monitoring are obstacles to the optimization of SIKS-NG. The novelty of this study lies in the descriptive qualitative approach that reveals the direct experiences of stakeholders in using the application. Implications of these findings suggest the need for improvements in program socialization and monitoring so that SIKS-NG can function optimally and provide maximum benefits to the community in managing poverty data and improving public services in the field of social welfare. Highlights: Assessing the effectiveness of SIKS-NG in poverty data management. Highlighting issues with accuracy, socialization, and monitoring. Gathering direct experiences from users to inform improvements. Keywords: E-Government, SIKS-NG, Poverty Data, Social Welfare, Implementation Challenges